Treatment of Gingival Recessions Associated to Cervical Abrasion Lesions with Subepithelial Connective Tissue Graft: A Case Report - Deliberador, Tatiana M.; Bosco, Alvaro F.; Martins, Thiago M.; Nagata, Maria J. H. (European Journal of Dentistry, 2009)
Extensive gingival recessions associated with cervical abrasions are common among the population. Several different surgical and/or restorative therapies have been proposed to correct these lesions. This manuscript reports the treatment of multiple gingival recessions associatedto cervical abrasions. The procedure involved the utilization of subepithelial connective tissue graft (SCTG) combined with coronally advanced flap onto a previously restored root surface. At the postoperative follow-up visits, the success of the restorative/surgical approach was confirmed by the absence of bleeding to probing and periodontal pockets as well as presence of gingival tissue with normal color, texture and contouring. After 18 months of follow-up, the clinical conditions are stable with satisfactory root coverage and periodontal health. An excellent esthetical outcome was achieved and the patient is satisfied with case resolution. (Eur J Dent 2009;3:318-323)
Keywords: Periodontal healing; Periodontal regeneration; Restoration; Dental materials